A Mixed Ether Electrolyte for Lithium Metal Anode Protection in Working Lithium–Sulfur Batteries - Chen, Wei-Jing; Zhao, Chang-Xin; Li, Bo-Quan; Jin, Qi; Zhang, Xue-Qiang; Yuan, Tong-Qi; Zhang, Xitian; Jin, Zhehui; Kaskel, Stefan; Zhang, Qiang (Energy & Environmental Materials, 2020)
Lithium‒sulfur (Li–S) battery is considered as a promising energy storage system to realize high energy density. Nevertheless, unstable lithium metal anode emerges as the bottleneck toward practical applications, especially with limited anode excess required in a working full cell. In this contribution, a mixed diisopropyl ether-based (mixed-DIPE) electrolyte was proposed to effectively protect lithium metal anode in Li–S batteries with sulfurized polyacrylonitrile (SPAN) cathodes. The mixed-DIPE electrolyte improves the compatibility to lithium metal and suppresses the dissolution of lithium polysulfides, rendering significantly improved cycling stability. Concretely, Li | Cu half-cells with the mixed-DIPE electrolyte cycled stably for 120 cycles, which is nearly five times longer than that with routine carbonate-based electrolyte. Moreover, the mixed-DIPE electrolyte contributed to a doubled life span of 156 cycles at 0.5 C in Li | SPAN full cells with ultrathin 50 μm Li metal anodes compared with the routine electrolyte. This contribution affords an effective electrolyte formula for Li metal anode protection and is expected to propel the practical applications of high-energy-density Li‒S batteries.
CRIS-Team Scopus Importer:2022-04-14
Keywords: full cells; lithium anode protection; lithium‒sulfur batteries; mixed diisopropyl ether-based electrolyte; sulfurized polyacrylonitrile cathode